Studi Aspek Mikrobiologis Dan Kimiawi Minuman Jamu Gendong Kunyit Asam Di Jimbaran dan Kedonganan, Bali - Yolanda, Thanastasya; Trisna Darmayanti, Luh Putu; Selamet Duniaji, Agus (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2021)
“Jamu Gendong Kunyit Asam (Tamarind Turmeric Sour Herbs)” is a typical Indonesian drink that is quite famous which is one of the legacies of the Indonesian nation’s ancestors who have medicinal properties in maintaining health and for healing a disease. This study aims to determine aspects of chemistry and microbiology as well as food safety of Tamarind Turmeric Sour Herbs in Jimbaran and Kedonganan, Bali by using survey method and research. The observed variabels include total microbial, coliforms, Escherichia coli, pH, total acid, total vitamin C. The results of microbiological aspect test in this study showed that two samples of Jamu Gendong Kunyit Asam (Tamarind Turmeric Sour Herbs) at Jimbaran and Kedonganan,Bali does not meet the requirements according to SNI 7388:2009 namely samples B and E with indigo in sample B that is 30 x 10 -1 and sample E which is 1 x 10 -1 . The result of chemistry aspect are if the increase in total vitamin C will effect the increase in total acid and pH will be more acid. Besaide that, E. coli bacteria can grow at a pH of 5-7 and the compound content of the tamarind fruit is also antibacterial so that most of Jamu Gendong Kunyit Asam (Tamarind Turmeric Sour Herbs) at Jimbaran and Kedonganan are not contaminated with E.coli.